2011
DOI: 10.1093/toxsci/kfr253
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Reduction of Hippocampal Synaptic Transmission and Spines Following Exposure to Repeated Subclinical Doses of Organophosphorus Pesticide in Adult Mice

Abstract: Agricultural and household organophosphorus (OP) pesticides inhibit acetylcholinesterase (AchE), resulting in increased acetylcholine (Ach) in the central nervous system. In adults, acute and prolonged exposure to high doses of AchE inhibitors causes severe, clinically apparent symptoms, followed by lasting memory impairments and cognitive dysfunction. The neurotoxicity of repeated environmental exposure to lower, subclinical doses of OP pesticides in adults is not as well studied. However, repeated exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 66 publications
2
43
0
Order By: Relevance
“…It was concluded that CPF and CPO decrease axonal growth by interfering with the morphogenic activity of AChE. In support of these findings, Speed et al (2012) demonstrated that CPF decreased dendritic spine density in vivo following 5 days of exposure at 5 mg/kg/d, levels that inhibited hippocampal AChE by <10% after a single injection and by approximately 40% after 5 injections. Spine density was unaffected by CPF exposure when examined 1 week later.…”
Section: Mechanisms Of Chronic Op Neurotoxicitymentioning
confidence: 88%
See 1 more Smart Citation
“…It was concluded that CPF and CPO decrease axonal growth by interfering with the morphogenic activity of AChE. In support of these findings, Speed et al (2012) demonstrated that CPF decreased dendritic spine density in vivo following 5 days of exposure at 5 mg/kg/d, levels that inhibited hippocampal AChE by <10% after a single injection and by approximately 40% after 5 injections. Spine density was unaffected by CPF exposure when examined 1 week later.…”
Section: Mechanisms Of Chronic Op Neurotoxicitymentioning
confidence: 88%
“…Changes in length, number, or branching patterns of axons or dendrites have been linked to psychiatric manifestations in patients, including depression, anxiety, AD, and PD (Marsden, 2013; Rubia et al, 2014; Canu et al, 2015; Negrón-Oyarzo et al, 2016). Axonal length, neurite length, neurite number, and dendritic branching in neuronal culture systems have also been shown to be altered following exposure to a variety of OPs, including CPF (Howard et al, 2005; Yang et al, 2008; Speed et al, 2012), DZ (Pizzurro et al, 2014a,b), parathion (Yousefpour et al, 2006; Berríos et al, 2015), and T O CP (Chen et al, 2013; Duarte et al, 2016; Hausherr et al, 2016). For example, in primary cultures of sympathetic neurons, CPF inhibited axon outgrowth but promoted dendritic arborization (Howard et al, 2005).…”
Section: Mechanisms Of Chronic Op Neurotoxicitymentioning
confidence: 99%
“…Both human (Gulf War veteran populations) and animal studies have reported neurological outcomes associated with the exposures present during Gulf War deployment, including neuro-inflammation [16], changes in brain volume [17], hippocampal dysfunction [18,19], decreased white matter [7,9,20] and alterations in executive function and cognition [21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, symptoms of chronic OPs toxicity vary between headache, sweating, Parkinson's, alterations in memory, and psychiatric or neuropsychological dysfunction [15, 16]. In addition, the key findings of OPs toxicity in respiratory system include shortness of breath and rapidly progressive bradypnea leading to apnea due to loss of central inspiratory drive causing central failure of breathing [17].…”
Section: Introductionmentioning
confidence: 99%